Experimental research on spray evaporative cooling system applied to air-cooled chiller condenser - Hua Yang; Lan Rong; Xuanchen Liu; Liansheng Liu; Man Fan; Na Pei (Energy Reports, 2020)
This study investigates the performance of a refrigeration unit by applying a spray evaporative cooling system to an air-cooled chiller. Experiments are conducted in the temperate monsoon climate region by combining the spray evaporative cooling system with the air-cooled chiller. Moreover, this study adopts a new gas-liquid two-phase swirl nozzle, which is independently developed and characterized by high atomization quality and low energy consumption. The experimental results show that the power of the compressor is reduced, while the COP (Coefficient of Performance) of the air-cooled chiller increases by 4%-8% after the intervention of the spray evaporative cooling system. The spray cooling system contributes to an electricity savings of 2.37%-13.53% in air-cooled chiller systems. If a more reasonable spray evaporative cooling mode is used, such as controlling the water flows according to the cooling capacity and arranging the nozzle positions and angles reasonably, the COP of the air-cooled unit will be further improved.
Keywords: 330; Air-cooled chiller; Coefficient of performance; Evaporative cooling; Spray system